Warming delays the phenological sequences of an autumn‐flowering invader. Issue 12 (24th May 2018) - Peng, Yang; Yang, Jian‐Xia; Zhou, Xiao‐Hui; Peng, Pei‐Hao; Li, Jing‐Ji; He, Wei‐Ming
Abstract: Phenology can play an important role in driving plant invasions; however, little is known about how climate warming, nitrogen (N) deposition, and invasion stages influence the phenological sequences of autumn‐flowering invaders in a subtropical climate. Accordingly, we conducted an experiment to address the effects of experimental warming, N‐addition, and community types on the first inflorescence buds, flowering, seed‐setting, and dieback of invasive Solidago canadensis . Warming delayed the onset of first inflorescence buds, flowering, seed‐setting, and dieback; N‐addition did not influence these four phenophases; community types influenced the onset of first seed‐setting but not the other phenological phases. Seed‐setting was more sensitive to experimental manipulations than the other phenophases. The onset of first inflorescence buds, flowering, and seed‐setting was marginally or significantly correlated with ramet height but not ramet numbers. Our results suggest that future climate warming might delay the phenological sequences of autumn‐flowering invaders and some phenophases can shift with invasion stages. Abstract : Warming delayed the phenological sequences of an autumn‐flowering invader and its seed‐setting onset varied with invasion stages.